THE ANALYSIS OF DELL HYME’S SPEAKING IN FLIPPED MOVIE - Nafi'ah, Calista; Sabat, Christ Levionita; Silawati, Devi (Jurusan Sastra Indonesia, 2023)
This study looked at the SPEAKING theory as presented by Dell Hymes in the film Flipped. SPEAKING THEORY is a framework developed by Dell Hymes to prove how we use language. According to the theory, the way we communicate is heavily influenced by the context in which we use the language. The goal of this study is to analyze and explain SPEAKING divisions that occur in the film. Because the information is in the form of utterances, the descriptive qualitative method is used in this study. The author selects and analyzes three film conversations. The author focuses on the analysis of dell hyme speech in each conversation and discusses various sociolinguistic data. During this review, the data will be communicated in the findings.